Bioenergy From Agriculture: Challenges for the Rural Development Program in Sweden. Issue 12 (1st December 2016) - Waldenström, Cecilia; Ferguson, Richard; Sundberg, Cecilia; Tidåker, Pernilla; Westholm, Erik; Åkerskog, Ann
ABSTRACT: This article addresses the challenges for the EU Rural Development Program (RDP) to promote sustainable bioenergy production from agriculture. Drawing on the Swedish example, we identify opportunities for farmers and discuss agricultural-based bioenergy production in relation to the program objectives for agricultural competitiveness, sustainability and climate effects, and rural development. The sustainability and climate effects of agricultural-based bioenergy can be ascertained only through contextual analysis, and research indicates that rural development may be best promoted through local collaborative energy systems. Contrasting two ideal-type roles farmers may assume in bioenergy production, we discuss Swedish institutional contexts of energy production. In Sweden, the national energy policy tends to favor large-scale energy solutions and farmers taking on the roles as suppliers of primary products in large-scale energy systems. For RDP objectives to be realized, this tendency needs to be countered, local solutions need to be supported, and a national three-tiered energy policy integration needs to be furthered.